Methodological Guidelines for Structural Modeling in Marketing - A case Study of Ooredoo Company - Hachmi Baadj; Abdussalam Shibani (Dirassat Journal Economic Issue, 2024)
The purpose of this study is to determine the impact of corporate social responsibility on the brand equity of the company “Ooredoo”. Structural equations have become a key method and experimental means for the development of humanities using various advanced methods and technologies. The independent variables of the study are corporate social responsibility towards shareholders, environment, customers and local communities, and the dependent variable brand equity. To achieve the above objectives, a questionnaire was developed and distributed to a sample of (354) subjects. The collected data were analyzed using data analysis software (SMARTPLS). The study found that the impact of corporate social responsibility on Ooredoo's brand equity is approximately (32.2%). The study recommends businesses invest in CSR activities to create sustainable brands and achieve brand equity